2021
DOI: 10.1038/s41598-021-84479-0
|View full text |Cite
|
Sign up to set email alerts
|

Habitual fish intake negatively correlates with prevalence of frailty among patients with rheumatoid arthritis

Abstract: Frailty is a geriatric syndrome characterized by anabolic-catabolic imbalance and multisystem dysregulation resulting in increased adverse health outcomes, and is closely related with dietary habits in the general population. Although chronic inflammatory diseases are thought to accelerate development of frailty, correlations between rheumatoid arthritis (RA), frailty and dietary habits have not been examined. We performed a cross-sectional study using our cohort database (KURAMA cohort), and classified 306 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 34 publications
(29 reference statements)
2
31
0
Order By: Relevance
“…One study, using CDAI, found that this relationship was no longer evident after adjusting for age 33 . In contrast, two other studies, showed that frailty remained associated with a higher baseline DAS-28 score after adjustment for age, sex, duration of rheumatoid arthritis and physical impairment (quantified using the Health Assessment Questionnaire -Disability Index (HAQ-DI)) 25,27 .…”
Section: Rheumatoid Arthritis Disease Activitymentioning
confidence: 88%
See 2 more Smart Citations
“…One study, using CDAI, found that this relationship was no longer evident after adjusting for age 33 . In contrast, two other studies, showed that frailty remained associated with a higher baseline DAS-28 score after adjustment for age, sex, duration of rheumatoid arthritis and physical impairment (quantified using the Health Assessment Questionnaire -Disability Index (HAQ-DI)) 25,27 .…”
Section: Rheumatoid Arthritis Disease Activitymentioning
confidence: 88%
“…Ten studies, using seven different frailty measures and four different markers of rheumatoid arthritis disease activity (four using Disease Activity Score in 28 joints, two using the Rheumatoid Arthritis Disease Activity Index, two using Simple Disease Activity Index and two using Clinical Disease Activity Index) all showed a significant cross-sectional association between frailty status and activity of rheumatoid arthritis before adjustment for additional factors 10,11,20,21,25,[27][28][29][30]33 . One study, using CDAI, found that this relationship was no longer evident after adjusting for age 33 .…”
Section: Rheumatoid Arthritis Disease Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Each one rheumatologist per patient assessed and recorded RA disease activity including 28 tender and swollen joint sites in a template for electronic charts on every visit, and the obtained data were integrated with blood tests and other clinical information. We recruited female RA outpatients from the KURAMA cohort database [ 24 ]. Participants were enrolled from May 2014 to December 2014 who visited the Kyoto University Hospital, were over 18 years old, and met the diagnostic criteria of the ACR/EULRA RA classification [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…We measured muscle mass, muscle strength and physical performance to assess sarcopenia status in the study population, as previously described 10,22 . Skeletal muscle mass was measured by bioelectrical impedance analysis (Inbody 720: Biospace Co., Ltd., Seoul, Korea).…”
Section: Diagnosis Of Sarcopenia and Estimation Of The Related Parametersmentioning
confidence: 99%